(3Pe GdedGgis - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM GdeSfO GdeYR GdKbI HbjI GdGTjGN CHh GdefLi YHO Gddg Hf YeQ GdHZOGOi Yf GdfHi Udi Gddg Ydjg hSde Cfg bGd (B: ( (3JeSN WGFaI ef CeJi bQOg hWGFaI NfGRjQ(B) s
(3BNQgG (B:s
(3bGd Jdc caQI EfeG HOG bhe dhW Pdc UfYI GdQLGd HGdfSGA Ke UfYI GdQLGd HGdQLGd BNQ cJGH Pe GdedGgi dGHf CHj GdOfjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3Ydjg SeGYGJs
(3HBNQg ahGFO cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs